دية القتل الخطأ في الحوادث المرورية في الفقه الإسلامي: دراسة مقارنة Blood Money for Unintended Manslaughter in Traffic Accidents in Islamic Jurisprudence: A Comparative Study - القره داغي عارف علي عارف; بنت إسماعيل فايزة; آغا بابا ئاوات محمد (Journal of Islam in Asia (E-ISSN 2289-8077), 2015)
الملخّص يتعلق هذا البحث بموضوع دية القتل الخطأ في الحوادث المرورية في الفقه الإسلامي في العصر الحاضر لكثرة وقوعها وحاجة الناس إلى بيان أحكامها من حيث كيفية تقديرها. وتحرير الخلاف في دية المرأة، ومسألة دية الجنين في حال تعرضه للموت في بطن أمه نتيجة الحادث المروري، أو في حالة تعرضه للإجهاض والموت، وتناول أيضًا دية شخصين إذا ماتا نتيجة اصطدام سيارتين؛ فكيف تقدَّر الدِّية؟ وعالج البحث مسألة العاقلة في الوقت الحاضر التي تساعد الطرفين (الجاني والمجني عليه وذلك بجمع الدية وإعطائها للمجني عليه). وذلك من خلال استخدام المنهج الاستقرائي والمنهج المقارن: حيث يتم من خلاله جمع النصوص المتعلقة بالموضوع، وآراء العلماء المتقدمين، والمعاصرين، والمقارنة بينهما لمعرفة نقاط الاتفاق والاختلاف، لتجلية معالم الموضوع، وتسهيل مناقشتها بصورة دقيقة، ثم بيان الرأي الراجح. وقد توصلت الدراسة إلى أنَّ دية القتل في الحوادث المرورية في العصر الحاضر تساوي بالدينار الذهبي، الذي يساوي 4.250 جرامًا من الذهب، أو بما يساويها من النقد. وأنَّ الراجح هو تساوي دية الرجل مع دية المرأة. وفي حالة عدم وجود العاقلة لابأس من إنشاء شركة تعاونية لمساعدة من وقع منه الحادث. الكلمات المفتاحية: الدِّية، حوادث المرور، دية المرأة، دية الجنين، العاقلة. Abstract This research addresses the subject of blood money for unintended manslaughter in traffic accidents according to Islamic jurisprudence in the present era due to the frequency of their occurrence and the need for people to understand the legal provisions concerning determining the amount. In this regard, we seek to clarify the disagreements regarding the blood money for women and foetuses that die in the mother’s womb as a result of traffic accidents or abortion. We also address the issue of blood money for two people who die as a result of collision between two cars. We also examine the issue of ʿĀqilah (those who pay the blood money) who helped the two parties (the offender and the victim by collecting blood money and giving it to the victim). To clarify these issues, we use the inductive approach and comparative method wherein we collect the various texts on the subject, and the views of classical and contemporary scholars to engage in a comparison between them in order to identify the points of agreement and disagreement between views. From here, we also hope to identify the major factors pertaining to such issues in order to facilitate a precise and concrete discussion to arrive at the most correct opinion. The study found that blood money for manslaughter in traffic accidents in the present era is equal to a gold dinar, which is equal to 4.250 grams of gold, or its cash equivalent. We advocate that the correct view is that the amount of blood money paid to a man is equal to that of a woman, and that in the absence of an ʿĀqilah it is possible to form a cooperative or mutual fund to render assistance to the victim. Keywords: blood money, traffic accidents, women, foetus, ʿĀqilah.